Proportion of medication error reporting and its associated factors among healthcare workers in Indonesia: A mixed-methods study - Pramesona, Bayu Anggileo; Wardani, Dyah Wulan Sumekar Rengganis; Ramdini, Dwi Aulia; Taneepanichskul, Surasak (Belitung Nursing Journal, 2025)
Background: Medication errors (MEs) are among the most prevalent healthcare-related incidents. However, many institutions do not report these incidents. Objective: This study aimed to investigate the proportion of medication error reporting and the associated factors of medication error reporting among healthcare workers (HCWs) in the hospital settings. Methods: This mixed-methods study used a sequential explanatory design. The quantitative phase involved 122 HCWs, including physicians, nurses, midwives, and pharmacists/pharmacist assistants, and the qualitative phase purposively included 15 of these participants. Data were collected from June to July 2024 at a public hospital in North Lampung, Indonesia, using a self-administered questionnaire and face-to-face in-depth interviews. Quantitative data were analyzed using logistic regression, and qualitative data were analyzed using thematic analysis. Results: The proportion of medication error reporting among HCWs was found to be 64.7%. Lack of a readily available system for reporting medication errors and fear of being blamed were considered as two of the most common causes of HCWs being hindered from reporting MEs. The logistic regression analysis showed that having experienced any medication administration error and having discovered medication error cases that others committed were significantly associated with medication error reporting. From qualitative data, eight themes emerged: 1) monitoring and evaluation, 2) teamwork, 3) self-motivation, 4) organizational culture, 5) rewards and penalties, 6) lack of facilities, 7) lack of understanding about MEs, and 8) fears. Conclusion: The study found a relatively high rate of medication error reporting, indicating that HCWs have an intrinsic motivation to report. However, systemic barriers, such as the lack of a supportive infrastructure and fear of retribution, remain major challenges. Developing a user-friendly, digital medication error reporting system with an anonymous option is recommended to mitigate fear and providing institution-wide training on patient safety culture and reporting procedures to address knowledge gaps.